The validity of contemporary rational structures in the principled thought of Imam Khomeini - Mansoor Gharibpoor; Seyyed Mahdi Jokar; Roosta Zohrab (مطالعات فقه و حقوق اسلامی)
The emergence of newly created institutions leads to the formation of new rational structures, which it seems necessary to examine their validity in order to solve emerging issues. The issue is, what is the validity of this range of buildings? It is assumed that contemporary intellectual structures have intrinsic validity. Famous scholars believe in the non-intrinsic validity of rational constructions, so they face restrictions and difficulties in confronting invented constructions and discovering the consensus of the Shariah. The positive result of the upcoming research is the unpopular theory, that is, the inherent validity of rational structures, especially contemporary rational structures. By looking carefully at the Usuli works of Imam Khomeini (RA), the conclusion is reached that the view of His Holiness is different from the Usuli scholars. In this way, they adopted the theory of non-deterrence in relation to non-invented constructions while accepting the validity of credit. But regarding the contemporary rational constructions, it can be said that it believes in the inherent validity, because it is rationally (to us also rationally) acted on it, and failure to adhere to them leads to difficulties and embarrassment and disruption of the system. The rule of attachment, grace and expediency element strengthen this view. The upcoming research has addressed this issue with an analytical and descriptive method.